2011
DOI: 10.1080/10942910903160422
|View full text |Cite
|
Sign up to set email alerts
|

Literature Data Compilation of WAI and WSI of Extrudate Food Products

Abstract: Published data on water absorption index and water solubility index of food materials are selected from the literature and organized into a database. Useful information such as the characteristics of the database and the statistics of the included data are presented. Researchers report that the values of the latter properties are affected by extrusion process variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 92 publications
(51 reference statements)
1
39
0
3
Order By: Relevance
“…The WSI value is an indication of state of protein in proteinaceous blends. Since, in our blend, the proportion of protein is high, the increase might be due to partial protein denaturation at higher temperature (Oikonomou and Krokida 2011). Kumar et al (2010) indicated that WSI increases with increase in fibrous content in the feed formulation, which supports our findings (Fig.…”
Section: Water Solubility Index (Wsi)supporting
confidence: 82%
See 1 more Smart Citation
“…The WSI value is an indication of state of protein in proteinaceous blends. Since, in our blend, the proportion of protein is high, the increase might be due to partial protein denaturation at higher temperature (Oikonomou and Krokida 2011). Kumar et al (2010) indicated that WSI increases with increase in fibrous content in the feed formulation, which supports our findings (Fig.…”
Section: Water Solubility Index (Wsi)supporting
confidence: 82%
“…The major functions of these ingredients are to give texture, structure, mouth feel, bulk, and many other characteristics desired for specific finished products (Launay and Lisch 1983). These characteristics are quantified by functional properties like bulk density, expansion index, water absorption and solubility indices and viscosity of the product (Singh et al 2007;Oikonomou and Krokida 2011). The effects of extrusion conditions and feed compositions on functional properties of various cereal and pulse based products have been studied extensively (Balasubramanian et al 2012;Seth and Rajamanickam 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The WSI of faba beans increased on sprouting (23.0–25.3%) (Table ). The WSI indicates the amount of molecules solubilised as an effect of processing (Oikonomou & Krokida, ). Roasting increased WSI of barley which could be attributed to molecular fragmentation on starch gelatinisation and disruption of the cell wall materials and similar was reported on barley roasting (Sharma et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…In particular, the first group refers to the initial composition of raw material, raw material formulation, pre-processing treatments and initial particle size of milled materials. The second group is related to the extruder conditions, such as extruder type, last section barrel temperature, feed moisture content, feed rate, screw speed, screw configuration, screw compression ratio, die dimension, and die configuration (ShaRMa et al, 2004;oIkoNoMou & kRokIDa, 2011).…”
Section: Resultsmentioning
confidence: 99%